PENGEMBANGAN BLOG UNTUK MENDUKUNG PEMBELAJARAN PADA MATA KULIAH MEDIA PEMBELAJARAN MATEMATIKA - Fajriah, Nurul; Zulkardi, Zulkardi; A. Siroj, Rusdy (JURNAL e-DuMath, 2017)
Abstract: This study aims to produce a blog that supports learning on Mathematics Media Learning courses a valid and practical, as well as knowing the potential effects that arise from the development of the students ability of blogs to make math learning media. Research methods used are design research with development study type. The subject of this research is the 4th semester students of mathematics education STKIP PGRI Bandar LampungÂ  consists of 42 students. Data collection technique at preliminary stage is the analysis of documents, whereas in the formative evaluation are walktrough, observation, interviews, and a question form. The conclusions of this study are (1) Mediatikaâs blog has been produced to support learning in Mathematics Learning Media courses; (2) through the use of learning blog Mediatika, students are able to make math learning media which has produced 9 math learning medias.Keywords: Blog, Media Of Learning Mathematics (MPM), Development Research